2000
DOI: 10.1021/bi992091m
|View full text |Cite
|
Sign up to set email alerts
|

Rational Modification of Protein Stability by the Mutation of Charged Surface Residues

Abstract: Continuum methods were used to calculate the electrostatic contributions of charged and polar side chains to the overall stability of a small 41-residue helical protein, the peripheral subunit-binding domain. The results of these calculations suggest several residues that are destabilizing, relative to hydrophobic isosteres. One position was chosen to test the results of these calculations. Arg8 is located on the surface of the protein in a region of positive electrostatic potential. The calculations suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
149
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 196 publications
(156 citation statements)
references
References 41 publications
7
149
0
Order By: Relevance
“…PB calculations have been used successfully to engineer proteins with higher stability (34,35), but to best of our knowledge the same method as here has not been used much for engineering higher affinity for ligand binding. A related Tanford-Kirkwood electrostatic model (36) has been used in design of specificity of coiled-coil recognition, whereas a previous study (37) used continuum calculations to design cytokine variants with pH-dependent loss of affinity by a histidine-switch.…”
Section: Discussionmentioning
confidence: 99%
“…PB calculations have been used successfully to engineer proteins with higher stability (34,35), but to best of our knowledge the same method as here has not been used much for engineering higher affinity for ligand binding. A related Tanford-Kirkwood electrostatic model (36) has been used in design of specificity of coiled-coil recognition, whereas a previous study (37) used continuum calculations to design cytokine variants with pH-dependent loss of affinity by a histidine-switch.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins can be engineered to be more stable in vitro with few mutations, by introduction of specific bonds (39,40) or favorable interactions (41)(42)(43). However, it has been shown that in vitro protein stabilization based on local stabilization of a secondary structural element can strengthen not only the final F state but also a small set of discrete partially folded native-like intermediates (41).…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we present the results of rational design of enzymes with enhanced stability and unchanged enzymatic activity. This approach has 2 major differences from previously described successful protein design methods (2)(3)(4)(5): (i) it concentrates only on the residues on the protein surface, and (ii) it optimizes just one type of interactions, namely, charge-charge interactions on the protein surface (6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%